El termino alumnus indicador de dependencia personal en la Hispania romana (Minerva, 2019)
In the epigraphical sources of Roman Spain there are some individuals who receive the common name of alumnus. This people belong to a social status of personal dependency (slaves or freemen). The term alumnus involves a situation quite similar to adoption. A dominus takes on the upbringing of children and teenagers who had a previous legal existence, and from that moment they come under the tutelage of the new owner. After a critical survey of the sources and a detailed examination, the results of this investigation must be connected to those obtained by this author in his studies about the name Thophimus, establishing the similarities and differences between both cases.